Hubungan Penguasaan Kosakata dengan Keterampilan Menulis Argumentasi Siswa Kelas X SMA Negeri 6 Padang - Septriyanti, Yesi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article aims to (1) describe mastery of vocabulary of class X students of SMA Negeri 6 Padang, (2) describe the argument essay writing skill of class X students of SMAN 6 Padang, (3) analyze the relationship between mastery of vocabulary with the argument essay writing skill of class X students of SMAN 6 Padang. The type of the study was descriptive quantitative research method and correlational approach. The data of this study were obtained using the test. The objective test was used to collect the data. The findings of the study showed relationship between the mastery of vocabulary with the argument essay writing skill of class X students of SMAN 6 Padang with correlation coefficient was 0,687.